Experiences of Parents Nursing Their Neonates on End-Of-Life Care in Neonatal Intensive Care Unit at Women and New-Born Hospital- University Teaching Hospitals, Lusaka Zambia - Lungowe, Mwanamwalye; Mwape, Lonia; Masumo, Maureen (International Journal of Health Sciences, 2025)
Purpose: The aim is to explore the experiences of parents nursing their neonates on end-of-life care in NICU at women and new-born hospital, University Teaching Hospitals. Methodology: Qualitative descriptive phenomenological approach was used. It was used to appreciate the experiences of parents nursing their neonates on end-of-life care in NICU, Women and New-born hospital. The target population of this study were parents who nursing their neonates in neonatal intensive care unit at Women and new born hospital, University Teaching Hospitals, Lusaka Zambia. The interview guide was used for data collection. Data was later coded to come up with sub themes. And themes emerged form sub themes. Thematic analysis was used to analyse data. Results were then presented in tables. Findings: Main findings indicated that parents (10) experienced both psychological and emotional problems such as, anxiety, stress, worry, hopelessness, confusion, anger, crying, sadness, frustration, dissatisfaction, happiness, regret, compliant, disappointment, bad feeling, self-blaming, nervousness, disturbance, and lack of self-control. In addition, the study revealed that parents suffered from inadequate emotional support and quality of care as nurses working in the Neonatal Intensive Care Unit were not readily available to give them emotional support, and lack of space to take a nap as the hospital only provides for the patients (neonates). Contribution to Theory, Policy and Practice: The study concluded that parents nursing their neonates on end-of-life care in NICU at Women and New-born Hospital had both good and bad experiences each day that passes. Other findings indicated that parents experienced both psychological and emotional problems such as, anxiety, stress, and worry. The study recommended; the development of universal practices to minimize the negative experiences of parents. Furthermore, the other recommendation is counselling and spiritual support for parents to strengthen them through the hospital stay. Also, the hospital should provide training on compassionate and respectful care for healthcare providers to enhance parent-healthcare provider communication and supports. Other researchers in future, can look at the experiences of healthcare staff when nursing the neonates on end -of- life care.